(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
About 50% of medications/drugs have obstacle of poor solubility, poor oral bioavailability, due to enzymatic/gastric degradation in the gastrointestinal tract pH, high pre-systemic intestinal and hepatic metabolism, permeability, small absorption window, and short residence duration at the absorption location. Niosomal drug deliveries have specific advantages over conventional dosage form with respect to improvement in bioavailability. Niosomes are colloidal particles created when non-ionic surfactants self-assemble in an aqueous solution to form closed bilayer structures. The various methods are reported until today for the preparation of niosomes; ether injection method, thin film hydration method, sonication method, microfluidization, multiple membrane extrusion method, reversephase evaporation technique, transmembrane Ph. Gradient drug uptake process (remote loading), the bubble method, freeze-thaw method, emulsion method, and formation of niosomes from proniosome. The current review article focused on the preparation and evaluation of niosome drug delivery and its advantages over conventional drug delivery. The niosomal drug delivery was found to be best for solubility and bioavailability enhancement of poorly water-soluble drugs.